Electrodialysis for lithium recovery from brine: process configurations, techno-economic analysis, challenges and opportunities with artificial intelligence - Liang, Y. Y.; Li, M (Elsevier Ltd, 2025)
This review explores the current state of electrodialysis (ED) for lithium recovery, emphasizing process configurations, mechanisms, performance and key efficiency factors. Conventional ED faces challenges such as low ion selectivity and membrane fouling, while Bipolar Membrane ED offers enhanced pH control and lithium recovery but is hindered by high energy consumption and membrane instability. Selective ED improves lithium selectivity using monovalent ion-selective membranes but is limited by high costs, scaling and batch operation. Redox-Couple ED, still in its early stages, requires further development for industrial scalability. The review highlights the importance of optimizing operational parameters, including voltage, current density, pH, flow rate and temperature to enhance ion migration and minimize inefficiencies. A techno-economic analysis shows the potential of ED-based lithium production to be cost-effective, though large-scale viability remains uncertain. Membrane fouling, caused by scale-forming ions, can be mitigated through pretreatment and cleaning methods, but further research is necessary to improve membrane durability and performance. Despite ED's environmental advantages, innovations such as introducing CO2 into the ED catholyte to produce Li2CO3, thereby eliminating the need for sodium carbonate as a precipitator show promise for reducing energy consumption. Finally, research directions on artificial intelligence (AI) for extracting lithium using ED are provided.